Magnetic mineral dissolution recorded in a lacustrine sequence from the Heqing Basin, SW China, and its relationship with changes in the Indian monsoon. (February 2020) - Xu, Xinwen; Qiang, Xiaoke; Zhao, Hui; Fu, Chaofeng
Graphical abstract: Highlights: Magnetic dissolution reduced the concentration of magnetic oxides in the lake sediments. Strong magnetic mineral dissolution was associated with high Antarctic temperature. Dry climate at ~320 ka in the Heqing Basin was linked to strengthened Indian Ocean Dipole. Abstract: The dissolution of magnetic oxides is an important process in many lake environments. Understanding this phenomenon is crucial for the paleoenvironmental interpretation of the magnetic properties of lake sediments. In order to reveal its effects on sedimentary magnetic properties, and to assess the possible associated paleoenvironmental implications, we carried out detailed rock magnetic analyses of the selected samples from a 920-kyr lacustrine sequence from the Heqing Basin, SW China. The results indicate that the sedimentary magnetic properties are controlled by the concentration and grain size of magnetite and maghemite. High magnetic susceptibility (χ) intervals contain more fine-grained magnetite and maghemite, while low χ intervals contain only minor amounts of residual magnetite. The decreased content of fine-grained maghemite from high χ to low χ intervals reflects the dissolution of magnetic oxides during deposition. Intervals affected by strong magnetic dissolution have a high TOC content and correspond to times of high Antarctic temperatures, suggesting that magnetic mineral dissolution intensity was associated with variations in the strength of the Indian Summer Monsoon (ISM). Notably, the ISM is sensitive to Southern Hemisphere warming. Weak magnetic dissolution indicates a dry climate occurred since ~320 kyr in the Heqing Basin. This dry/cool event was widespread across the Eastern Bay of Bengal, Equatorial Indian Ocean and Northern Australia, and was linked to a strengthened Indian Ocean Dipole (IOD). Since the moisture source of the Heqing Basin was mainly from the above regions, we infer that the influence of the IOD extended northwards to SW China.